Photocatalytic Activity of Ti-SBA-15/C3N4 for Degradation of 2,4-Dichlorophenoxyacetic Acid in Water under Visible Light - Hoa T. T. Duong; Mai T. P. Duong; Oanh K. Nguyen; Son T. Le; Long V. Dang; Binh T. Nguyen; Dang V. Do (Journal of Analytical Methods in Chemistry)
In the present study, the photocatalytic activity of Ti-SBA-15/C3N4 catalysts was investigated to degrade 2,4-Dichlorophenoxyacetic acid (2,4-D) herbicides in water under visible light irradiation. The catalysts were synthesized via a simple hydrothermal method and characterized by various analytical techniques, including SAXS, N2 adsorption-desorption isotherms, Zeta potential, PL, FT-IR, XRF, TGA, and UV-DRS. Our study indicated that the 2.5Ti-SBA-15/C3N4 had higher efficiency in the degradation of 2,4-D than Ti-SBA-15 and C3N4. The decomposition of 2,4-D reached 60% under 180 minutes of visible light irradiation at room temperature on 2.5Ti-SBA-15/C3N4. Moreover, the degradation of 2,4-D on Ti-SBA-15/C3N4 was pseudo-first-order kinetics with the highest rate constant (0.00484 min−1), which was much higher than that obtained for other photocatalysts reported recently. Furthermore, the catalyst can be reused at least two times for photodegradation of 2,4-D solution under visible light irradiation within a slight decrease in catalytic activity.